Influence of three different dentin bonding agents on the adhesion of composite resin to dentine-An in vitro study - Christina Hoferichter; Stefan Rüttermann; Susanne Gerhardt- Szep (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
The demand for aesthetic, durable and quality restorations has increased signifi cantly. Teeth should be unobtrusive and ideally minimally invasive reconstructed. It is a problem to get a permanent bond between the hydrophilic dentin and the hydrophobic composite [1,2]. Dentin adhesives play a key role in this [3-6]. In order to have feedback on the bond between composite materials and hard tooth substance, in vitro scientifi c studies are carried out. The experimental setups differ in many parameters in the studies and are therefore often not comparable.